Exploring Challenges Faced ny Students in Translating Four English Text Genres (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Translation is not an easy task every translator inevitably faces several difficulties, such as language problems, grammar, and cultural elements in the target language. This study is aimed to investigates the challenges encountered by students in translating English text, focusing on secondary school contexts in Indonesia. This study employed a systematic literature review methodology, the study identifies and analyses difficulties in translation through a five-phased approach. The findings reveal a various obstacle, including linguistic barriers, cultural disparities, and grammatical complexities. The analysis underscores the necessity for targeted interventions to address these challenges and enhance students' translation proficiency. Furthermore, the study emphasizes the importance of linguistic competence, particularly in grammar and vocabulary, in overcoming translation difficulties.